Rancang Bangun Sistem Informasi Penggajian Karyawan Di Toko Aston Printer - Susanto, Edy; Susena, Edy; Maozyonzyah, Adit Saputra (Politeknik Indonusa Surakarta, 2022)
Aston Printer Klaten store in 2021 requires an employee payroll system to perform salary calculations. In the current system, data management in terms of salary calculations is still manual and not computerized properly, so the payroll process is often wrong and too late to be given to employees by calculating salaries based on hours of arrival, targets that have been achieved, overtime and permits. The purpose of this system is to make it easier to do payroll, to facilitate the process of calculating payroll for employees. The method used is the waterfall method starting from the work of a system that is carried out sequentially or linearly with needs analysis, system design, program coding, program testing, program implementation. In collecting data the author uses the method of observation, interviews, literature study and documentation. The final result obtained by the creation of an information system for calculating the salary of the Aston Printer Klaten Shop by applying this Laravel framework, the admin of the Aston Printer Klaten store can report financial reports to the owner. With the results of the system that can be accessed by admin and owner, namely employee data and salary management data.